3D Robotic Control of Micro-scale Optical Swarms at an Interface - Carlisle, N; Nock, V; Williams, MAK; Whitby, CP; Chen, JLY; Avci, E (Institute of Electrical and Electronics Engineers, 2025)
Optical force-induced assembly is a promising yet scarcely explored approach for developing functional tools and objects at the microscale, with a wide range of potential applications. Our previous work was the first to investigate the manipulation of these assemblies in the XY plane. Here, we expand on these techniques by systematically exploring optical trap manipulation with the addition of Z-axis control. Manipulation of the Z-axis is referred to as axial displacement and is a viable approach for actively manipulating the assembly morphology. Experiments are conducted for the first time to explore and detail the response of the assembly during active 3D trap manipulation, informing the development of an autonomous control algorithm over the 2D area of the assembly during motion. This control presents techniques to increase assembly stability or alter the area of the assembly for tasks such as passing through constrictions. This work aims to develop the control techniques required to create a unique micromanufacturing approach inspired by the Kilobot thousand-robot swarm.
Keywords: 4007 Control Engineering, Mechatronics and Robotics; 40 Engineering; 0913 Mechanical Engineering; 4007 Control engineering, mechatronics and robotics; 4602 Artificial intelligence